PLANT RESOURCE UTILIZATION AND CONSERVATION STRATEGIES AMONG RURAL COMMUNITIES OF GWANDUM, SHONGOM LGA OF GOMBE STATE - JACOB, J. A.; MICAH, E.J. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
In this study, we obtained an in-depth ethnobotanical studies in some selected rural communities of Shongom Local Government Area of Gombe State to close this knowledge gap. Information was obtained from 98 individuals through interviews using semi-structured questionnaire and group discussions, supplemented with field observations. A total of 34 ethnobotanically important plant species belonging to 18 families (92% indigenous and 8% exotics) mostly from the Fabaceae, Arecaceae, Anacardiaceae, Combretaceae, and Moraceae were documented. These plant species were mainly utilized for food, medicine, fodder, construction and fencing purposes. Significantly used species were Moringa oleifera (Linn), Adansonia digitata, Ficus thonningii, Anogeissusleio carpus, Dioscorea Spp, Parkia biglobosa and Mangifera indica. Only 25 (%) of the species reported had their status assessed by the International Union for Conservation of Nature (IUCN). Local social beliefs, taboos, fines as well as traditional rules and regulation are in place to aid the management of communal resources. However, a significant number (62%) of participants mentioned that they were not pleased with the rule and regulations. This study concluded that plant resources still play a crucial role in rural villages of Shongom Local Government Area. Furthermore, for utilization and effective long-term conservation of these plant species, government implemented conservation measure alongside awareness creation are highly recommended.